Distinct immunity protein families mediate compartment-specific neutralization of a bacterial toxin - Felicity Alcock; Yaping Yang; Justin Deme; Guillermina Casabona; Chriselle Mendonca; Fatima Ulhuq; Susan Lea; Tracy Palmer (Cell Reports, 2025)
Summary: Staphylococcus aureus utilizes a type VII secretion system (T7SS) to secrete antibacterial toxins targeting competitor bacteria. EsxX is a T7SS substrate protein harboring an N-terminal LXG domain, which is secreted by ST398 strains. We demonstrate that the EsxX C terminus is a membrane-depolarizing toxin with a glycine zipper motif. EsxX is profoundly toxic to bacteria, displaying toxicity from both cytoplasmic and extracellular compartments. A pair of polytopic membrane proteins, ExiCD, protects cells from intoxication by extracellular EsxX. By contrast, a distinct soluble heterodimer, ExiAB, neutralizes cytoplasmic EsxX by sequestration of its glycine zipper motif in a binding groove on ExiB. exiA-exiB co-occur with esxX, consistent with protection from self-toxicity prior to EsxX secretion. By contrast, ExiCD is encoded by both EsxX producers and in antitoxin islands of competitor strains that do not encode EsxX, consistent with providing immunity against the secreted form of the toxin.